Modelagem de sistemas de manufatura usando Redes de Petri Coloridas Fuzzy focando a solução de conflitos - Sgavioli, Mayra (2010)
A Flexible Manufacturing System is a production system where more than one event can occur simultaneously in parallel, asynchronously or concurrently. These are designed to meet the needs of the market, demand for improved product quality, lower costs and shorter delivery times. Due to the complexity and flexibility of these systems, conflicts can occur when more than one process requests the same resource, such as machines or AGVs, or when a product can be produced in more than one production routing. Thus, a conflict resolution policy is needed in this type of environment. This study uses Fuzzy Coloured Petri Nets for modeling a manufacturing system. The manufacturing system is modeled considering the resources, buffers, production routings, AGV routes and identifying conflict points. The conflict resolution is performed considering both information on the shop floor and production management. Fuzzy rules are constructed to prioritize conflicting processes and a fuzzy rule-based system is modeled on Fuzzy Coloured Petri Nets in the same network as the manufacturing system, making the model of the system independent of other systems of support for the resolution of conflicts. In this work we considered the conflicts that can occur when loading and unloading station and the input and output buffer. According to the source of conflict, a rule base is shaped to assign priorities to processes. From this model it is possible to make the control system and ensure that identified conflicts are resolved.